Study of antimicrobial activity and mechanism of vapor-phase cinnamaldehyde for killing Escherichia coli based on fumigation method - Duan, Xuejuan; Qin, Dongying; Li, Hongming; Zhang, Tong; Han, Yali; Huang, Yu qiang; He, Dong; Wu, Kegang; Chai, Xianghua; Chen, Chun (Frontiers in Nutrition, 2022)
The vapor-phase antibacterial activity of essential oils makes them suitable for applications in air disinfection and other fields. At present, vapor-phase antibacterial activity of plant-based essential oils has rarely been reported. Herein, we report a new approach to investigate the antimicrobial activity and mechanism of vapor-phase cinnamaldehyde using Escherichia coli (E. coli) and three other pathogenic bacteria (Pseudomonas aeruginosa, Salmonella, Staphylococcus aureus) as model bacteria. Plate fumigation and agar block transfer techniques were used to determine the antimicrobial activities of vapor-phase cinnamaldehyde fumigation on the four types of bacteria, and the mechanism of action was determined by electrical conductivity (EC), OD260nm measurement, transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and fluorescence spectroscopy. Cinnamaldehyde had good vapor-phase antibacterial activity against the four types of bacteria. The TEM, EC, and OD260nm measurements showed that after fumigation with cinnamaldehyde, the ultrastructures of the cells were damaged, and plasmolysis, cell collapse, and leakage of intracellular substances were observed. The FTIR and fluorescence spectroscopy analyses showed that the secondary and tertiary structures of bacterial membrane proteins were altered. These findings indicate that the cell membrane is an important target for plant-based essential oils to exert their vapor-phase antimicrobial effects. The results showed that plant-based essential oils can be developed as volatile broad-spectrum disinfection products and vapor-phase antiseptics.